Short Symmetric-End Antimicrobial Peptides Centered on β-Turn Amino Acids Unit Improve Selectivity and Stability - Dong, Na; Chou, Shuli; Li, Jiawei; Xue, Chenyu; Li, Xinran; Cheng, Baojing; Shan, Anshan; Xu, Li (Frontiers in Microbiology, 2018)
Antimicrobial peptides (AMPs) are excellent candidates to combat the increasing number of multi- or pan-resistant pathogens worldwide based on their mechanism of action, which is different from that of antibiotics. In this study, we designed short peptides by fusing an α-helix and β-turn sequence-motif in a symmetric-end template to promote the higher cell selectivity, antibacterial activity and salt-resistance of these structures. The results showed that the designed peptides PQ and PP tended to form an α-helical structure upon interacting with a membrane-mimicking environment. They displayed high cell selectivity towards bacterial cells over eukaryotic cells. Their activities were mostly maintained in the presence of different conditions (salts, serum, heat and pH), which indicated their stability in vivo. Fluorescence spectroscopy and electron microscopy analyses indicated that PP and PQ killed bacterial cells through membrane pore formation, thereby damaging membrane integrity. This study revealed the potential application of these designed peptides as new candidate antimicrobial agents.